Optimasi Polivinilalkohol (PVA) Sebagai Basis Sediaan Gel Antijerawat - Nur Aprilianti; Hajrah Hajrah; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
The gel is one of the preparations that are considered suitable for skin conditions with excessive sebaceous gland function. Polyvinylalcohol (PVA) is one of the gelling agents that can from a layer or film that is very strong and plastic to give good contact between the drug and the skin. This study aims to find the best concentration of polyvinylalcohol (PVA) as a gel base. Each formula was made using four variations of polyvinylalcohol (PVA) concentrations of 6%, 8%, 10%, and 12% and tested the physical properties that include organoleptic test, pH, homogeneity, spreadability, and viscosity. The results showed that the optimum of base formula contains a concentration of polyvinylalcohol (PVA) base of 6% and 8%.